The historical record of massive star formation in Cygnus - Comerón, Fernando; Djupvik, A. A.; Schneider, N.; Pasquali, Anna (Astronomy and astrophysics, 2020)
Context. The Cygnus region, which dominates the local spiral arm of the Galaxy, is one of the nearest complexes of massive star formation, extending over several hundred parsecs. Its massive stellar content, regions of ongoing star formation, and molecular gas have been studied in detail at virtually all wavelengths. However, little is known of the history of the region beyond the past 10 Myr. Aims. We use the correlations between age, mass and luminosity of red supergiants to explore the history of star formation in Cygnus previous to the formation of the present-day associations. The brightness and spectroscopic characteristics of red supergiants make it easy to identify them and build up a virtually complete sample of such stars at the distance of the Cygnus region, thus providing a record of massive star formation extending several tens of Myr into the past, a period inaccessible through the O and early B stars observable at present. Methods. We have made a selection based on the 2MASS colors of a sample of bright, red stars in an area of 84 square degrees covering the whole present extension of the Cygnus association in the Local Arm. We have obtained spectroscopy in the red visible range allowing an accurate, homogeneous spectral classification as well as a reliable separation between supergiants and other cool stars. Our data are complemented with Gaia Data Release 2 astrometric data. Results. We have identified 29 red supergiants in the area, 17 of which had not been previously classified as supergiants. Twenty-four of the 29 most likely belong to the Cygnus region and four of the remaining to the Perseus arm. We have used their derived luminosities and masses to infer the star formation history of the region. Intense massive star formation activity is found to have started approximately 15 Myr ago, and we find evidence for two other episodes, one taking place between 20 and 30 Myr ago and another one having ended approximately 40 Myr ago. There are small but significant differences between the kinematic properties of red supergiants younger or older then 20 Myr, hinting that stars of the older group were formed outside the precursor of the present Cygnus complex, possibly in the Sagittarius-Carina arm.
Gesehen am 15.01.2021
Based on observations collected at the Centro Astronómico His-pano Alemán (CAHA) at Calar Alto, operated jointly by the Junta deAndalucía and the Instituto de Astrofísica de Andalucía (CSIC)